Improving Students’ Vocabulary through Make a Match Technique and Number Head Together (A Classroom Action Research at SMP Negeri 2 Langowan) - Tini Mogea; Salaki Reynaldo Joshua (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The purpose of this study is to increase students' vocabulary through "make a match" and "number head together" techniques with the students of SMP Negeri 2 Langowan. The sample was composed of 25 first-grade students. This study is classified as "action research" because it is conducted in a cycle. The first grade students were taken as samples for this research. The instruments used to collect data consisted of a reflective journal, field notes, and tests. The data were analyzed in a way that triangulates the data sources. The result shows that with the application of the "make a match" technique in Cycle 1, only a very few students gained progress in vocabulary with a mean score of 5.52. By applying the "number head together" technique in Cycle 2, more students were able to understand and use vocabulary. It was shown in this cycle that there was some progress made by the students in acquiring reading competency, with the mean score of the test being 6.56. By applying the Make, a Match technique and the Number Heads Together technique in Cycle 3, most of the students made great progress, with a mean score of 8.04.